ANALISIS KEPATUHAN PEMBIAYAAN MUDHARABAH DALAM PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK NO.59) TERHADAP ASPEK SYARIAH ILMU FIQIH SYAFI’IYAH - Atieq Amjadallah Alfie; - Khanifah (AKSES: Jurnal Ekonomi dan Bisnis, 2007)
Statement of Finacial Accounting Standart (PSAK) N0.59 representing order about method of copilation of financial statement released by institute owningauthority for that, that isTying of Indonesia Accountant (IAI) . PSAK No.59 this explain about finacial accounting of bangking of Moslem law one of them is about mudharabah, because mudharabah is often used in activity of banking business hence need the axistence of study repeat about mudharabahin PSAK No.59. This research type is book study descriptively is analitif. Method used in analysing compliance of defrayal mudharabah at PSAK No.59 to science of Fiqh Syafi’iyah steming from data sekunder, that is book, result of seminar, internet, pictures etc.Result from this research indicate that the statement mudharabah in PSAK No.59 most have as according to Moslem law from facet of science of fiqh Syafi’iyah, but there are some paragraph which not yet as according to Moslem law of like paragraph no.15, 18,20 and 25 at PSAK No.59.Keywords : Mudharabah financing, accounting syariah.